Asymmetric Unilateral Vestibular Perception in Adolescents With Idiopathic Scoliosis - Woo, Emma J.; Siegmund, Gunter P.; Reilly, Christopher W.; Blouin, Jean-Sébastien (Frontiers in Neurology, 2019)
The cause of Adolescent Idiopathic Scoliosis (AIS) remains unclear, but one proposed cause of AIS is asymmetric vestibular function and the related descending drive to the spine musculature. The objective of this study was to determine if asymmetric vestibular function is present in individuals with AIS. Ten individuals with AIS (8F, 2M) and ten healthy age- and sex-matched controls were exposed to 10s-long virtual rotations induced by monaural or binaural electrical vestibular stimulation (EVS), and 10s-long real rotations delivered by a rotating chair. Using a forced-choice paradigm, participants indicated their perceived rotation direction (right or left) to stimuli of varying intensity. A Bayesian adaptive algorithm adjusted the stimulus intensity and direction to identify a stimulus level, which we called the direction recognition threshold, at which participants correctly identified the rotation direction 69% of the time. For unilateral vestibular stimuli (monaural EVS), the direction recognition thresholds were more asymmetric in all participants with AIS compared to control participants ([0.22 - 1.00 mA] vs [0.01 - 0.21 mA]; p < 0.001). For bilateral vestibular stimuli, however, the direction recognition thresholds did not differ between groups for either the real and virtual rotations (multiple p > 0.05). Previous reports of semicircular canal orientation asymmetry in individuals with AIS could not explain the magnitude of the vestibular function asymmetry we observed, suggesting a functional cause to the observed vestibular asymmetry. Thus, the present results suggest that a unilateral vestibular dysfunction is linked to AIS, potentially revealing a new path for the screening and monitoring of scoliosis in adolescents.